Curcumin Transethosome Gel: Anti-inflammatory Activity Test in Carrageenan-Induced Sprague Dawley Rat - Amalia, Anisa; Efendi, Kriana; Novianti, Amelia (Sanata Dharma University, 2024)
Curcumin has anti-inflammatory activities, and is formulated into the transethosome (TE) system to improve penetration. The TE system's stability can be increased by incorporating it into a gel dosage form. This study aims to determine the anti-inflammatory activities of curcumin TE gel. Curcumin TE gel was produced in 3 compositions, each having a curcumin content of 10 mg (F1), 40 mg (F2), or 160 mg (F3). On TE gels, organoleptic, viscosity, pH, particle size, and zeta potential were evaluated. The test animals were divided into five groups for anti-inflammatory activity testing. A 1% carrageenan solution was used to induce edema in the animals, and the volume of edema was measured for comparison with p0.05set as significant difference. Curcumin TE gel's physical properties showed a yellow and homogenous gel with viscosity values of 31.173 – 33.626 cPs, pH 4.75 – 4.84, particle size 208.3 – 319.4 nm, and zeta potential (-) 40.03 – (-) 51.12 mV. On anti-inflammatory tests, the edema volume in the group given curcumin TE gel decreased in the 270th minute. According to statistical analysis, the test group had a significant difference (p 0.05) from negative controls and no significant difference (p 0.05) from positive controls in F1 and F2 anti-inflammatory activity. According to these results, the curcumin TE gel exhibited anti-inflammatory activity equivalent to the positive control, while F3 had anti-inflammatory activity better than the positive control.